Comparative Analysis of regional architecture: education, theory, and practices of Rifat Chadirji and Sedat Hakki Eldem - kutlu divleli1, Melek; Mohd Nawawi, Norwina; Azmin, Aida Kesuma (Fatih Sultan Mehmet Vakif University Publications, 2019)
This paper raises the issue of a lack of awareness of significant regionalist architects from the Middle-east and neighbouring Muslim countries in comparison to Western architects. Hence, It aims to highlight on a comparative analysis between the life and works of two regional architects from the Middle-Eastern regions, Rifat Chadirji, an Iraqi, and Sedat Hakkı Eldem, from Turkey. Both have had a similar Western educational background, developed their ideologies and design theories in their architectural teachings and practices, concerning their countries' regional contexts. The objectives are (1) To establish the impacts of both of their lives and regional architecture manifestations towards their societies; and (2) to discover the unique regional interpretation and transformation of architectural design theory and ideology in their works-“Turkish House” and “Hamood Villa”. The research applied thematic qualitative data analysis, under the theme, "Regional Architecture", using descriptive and categorical comparative analysis between the two architects, based on social background, education and ideologies; precedent studies of their works, and expert interviews. The findings suggest that both architects have acquired a deep understanding of the roots of authentic regional expression while appreciating modernism's principles. They have also successfully synthesised form and function, which translate traditional architectural idioms into contemporary expressions, as inspirations for future regional architects generation. Their quest justifies the significance of regionalism architecture as a cultural and country's identity for any society in the world.